Carnauba bagana improves the soil quality cultivated with corn in the semiarid piauiense - Santos, Cássio de Moura; de Carvalho, Ana Clara Caminha; Araújo, Vinícius de Sousa; Nobre, Rafael de Sousa; Costa, Ana Karina Silva; Veloso, Ronilson Carvalho; Nunes, Lucila de Sousa; Silva, Daniel de Moura; Menezes, Maria do Socorro de Sousa; Rêgo, Irys de Moura; Rezende, Jefrejan (Disciplinarum Scientia | Naturais e Tecnológicas, 2023)
The Corn an important role in agriculture, and can be used in both human and animal food, production of ethanol, medicines and glue. However, is verified cultivation practices and soil inappropriate management have led to soil deterioration. Thus, the importance of vegetation cover and the incorporation of organic matter in these cultivated soils. The objective of this work was to evaluate the effect of Carnauba bagana maintained on the soil as mulch and incorporated in macrofauna and soil organic carbon, in the municipality of Itainópolis, in the semi-arid region of Piauí. The areas to be studied will be: corn area with carnauba bagana, as mulch and incorporated into the soil; corn area with uncovered soil and an area of preserved native vegetation. The epigean and edaphic macrofauna will be collected, sorted and identified at the order level. Soil samples will be collected to determine soil organic carbon. Carnauba bagana improved the macrofauna community and soil organic carbon content. The cultivation of corn on uncovered soil reduced the uniformity and diversity of the epigeal macrofauna, the Wealth and Abundance of the edaphic macrofauna and the soil organic carbon content. The variables Larvae, Abundance, Richness, Shannon and Pielou indices, and COS in layers 0.00-0.05 and 0.05- 0.10 m were selected for future studies of the impact of maize cultivation in the region.